THE MEDICAL TRADITIONS OF INDONESIAN- OSING- ETHNIC: TYPES OF LEXICAL MEANING OF TREAT VERB IN OSING LANGUAGES: TRADISI PENGOBATAN ETNIK OSING-INDONESIA: TIPE-TIPE MAKNA LEKSIKAL VERBA MENGOBATI DALAM BAHASA OSING - Asrumi Asrumi; Agus Sariono; Anastasia Erna Rochiati Sudarmaningtyas; Edy Hariyadi; Agustina Dewi Setyari (Jurnal Kata, 2022)
The purpose of this study is to reveal the types of lexical verbs that mean "to cure" and the forms of their distinguishing components in the Osing language in Banyuwangi Regency. The research data is in the form of a verb which means 'to cure', which is obtained through observation, interviews, and documentation methods, using note-taking and snowball techniques. The classified data were analyzed using the meaning component analysis method with lexical distinguishing characteristics in the form of actors, objects, ways, places, directions, frequency of activities, goals, focus, time, and tools with binary techniques (using the plus sign (₊) means having characteristics; a minus sign ( -) means uncharacteristically, and a plus-minus sign ((± ) means both characterized and uncharacterized, to find out the steps for treating medical, vein, and non-medical diseases. The results show that based on the method component, verb There are 25 types of treating in the Osing language.